2012
DOI: 10.5513/jcea01/13.3.1078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term potassium fertilization on the chemical composition of Oriental tobacco

Abstract: The effects of the different potassium rates (0, 75 and 450 kg K 2 O ha -1 ) on nutrient concentrations in the above-ground biomass and chemical characteristics of sun-cured tobacco have been studied in a stationary field trial. Annual fertilization with 75 kg K 2 O ha -1 was adequate to maintain soil K concentration near the initial value. It was found that yield of cured leaves was not significantly affected by rate of K application when oriental tobacco was grown on soils with high available soil K. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Various notable protective mechanisms in the utilization of microbial biostimulants under different stresses are osmolite production, phytohormone level modulation, increased antioxidant activity, and secretion of extracellular polymeric substances (EPS) under water stress such as flooding and drought [129][130][131]; phytohormone level modulation, emission of volatile organic components, ice nucleation activity antagonism, delay of senescence, and osmo and thermal protection under thermal stress such as freezing and extreme heat [132][133][134][135]; increased soil exploration and mineral nutrient solubilization under nutrient stress [136,137]; and induced system resistance, direct antagonism with pathogens, and phytohormone level modulation under biotic stress [138][139][140][141][142]. Bozhinova [143] reported that the application of the microbial inoculant Europlus ® and the protein hydrolysate (PH) Trainer ® increased the yield of tobacco by 5.5% and 6.7%, respectively, in comparison with untreated plants. Bozhinova [143] also noted that the application of the microbial inoculant Europlus boosted N, P, and K concentrations in leaves, and the concentrations of Ca, Mn, Zn, and Cu were slightly higher than the control treatment when the microbial inoculant Europlus was applied, and concluded that the use of microbial biostimulants in sustainable tobacco farming was effective in boosting the yield of oriental tobacco and the quality of cured leaves.…”
Section: Mechanisms Of Microbial Biostimulant Actionmentioning
confidence: 99%
“…Various notable protective mechanisms in the utilization of microbial biostimulants under different stresses are osmolite production, phytohormone level modulation, increased antioxidant activity, and secretion of extracellular polymeric substances (EPS) under water stress such as flooding and drought [129][130][131]; phytohormone level modulation, emission of volatile organic components, ice nucleation activity antagonism, delay of senescence, and osmo and thermal protection under thermal stress such as freezing and extreme heat [132][133][134][135]; increased soil exploration and mineral nutrient solubilization under nutrient stress [136,137]; and induced system resistance, direct antagonism with pathogens, and phytohormone level modulation under biotic stress [138][139][140][141][142]. Bozhinova [143] reported that the application of the microbial inoculant Europlus ® and the protein hydrolysate (PH) Trainer ® increased the yield of tobacco by 5.5% and 6.7%, respectively, in comparison with untreated plants. Bozhinova [143] also noted that the application of the microbial inoculant Europlus boosted N, P, and K concentrations in leaves, and the concentrations of Ca, Mn, Zn, and Cu were slightly higher than the control treatment when the microbial inoculant Europlus was applied, and concluded that the use of microbial biostimulants in sustainable tobacco farming was effective in boosting the yield of oriental tobacco and the quality of cured leaves.…”
Section: Mechanisms Of Microbial Biostimulant Actionmentioning
confidence: 99%
“…Ο φώσφορος επηρεάζει την ανάπτυξη των ριζών, την πρώτη ανάπτυξη του φυτού, και την ποιότητα των πρώτων φύλλων -βελτιώνει το χρώμα και την ποιότητα των φύλλων• συντηρητική εφαρμογή επιταχύνει την ανάπτυξη και την ωρίμανση (McCants and Woltz, 1967). Οι ρίζες του καπνού απορροφούν όχι μόνο η υψηλή ποσότητα ανόργανου φωσφόρου, αλλά και οργανικών κλασμάτων σε υψηλή συγκέντρωση φωσφορικών ενώσεων, οι οποίες παρατηρούνται και στα φύλλα (Bozhinova, 2016 Όπου: ns: µη σηµαντική (not significant) και *, **, *** σηµαντική τιµή σε p < 0,05, 0,01 και 0,001, αντίστοιχα.…”
Section: φωσφορικά φυτικού ιστούunclassified